The impact of mentoring on the Canadian early career teachers’ well-being - Kutsyuruba, Benjamin; Godden, Lorraine; Bosica, John (International journal of mentoring and coaching in education, 2019)
Purpose The purpose of this paper is to explore the impact that mentoring has on Canadian early career teachers’ (ECTs’) well-being. The authors describe findings from a pan-Canadian Teacher Induction Survey (n=1,343) that examined perceptions and experiences of ECTs within K–12 publicly funded schools, with particular interest in retention, career interests and the impact of mentoring on well-being. Design/methodology/approach An online survey was used to examine perceptions and experiences of ECTs within publicly funded K–12 schools across Canada. For this paper, the authors selectively analyzed 35 survey questions that pertained to mentorship and well-being of ECTs, using quantitative and qualitative procedures. Findings The findings revealed a strong correlation between the mentoring experiences and well-being of the participating Canadian ECTs. The teachers who did not receive mentorship indicated significantly lower feelings of well-being, and conversely, teachers who participated in some kind of mentorship demonstrated much higher levels of well-being. Research limitations/implications This paper draws on the selective analysis of the data from a larger study to elicit the connections between the mentoring support and perceived well-being. Due to inconsistencies in terminology and multifaceted offerings of induction and mentoring supports for ECTs across Canada, there might have been some ambiguity regarding the formal and informal mentorship supports. A longitudinal study that is designed to specifically examine the connection between the mentorship and well-being of ECTs could yield deeper understandings. A comparative study in different international contexts is commended. Practical implications The findings showed that the ECTs who did not receive any mentorship scored significantly lower feelings of well-being from external, structural, and internal well-being sources, and conversely, the ECTs who participated in some kind of mentorship scored much higher levels of feelings of well-being. Policy-makers should therefore continue to confidently include mentorship as an intentional strategy to support and help ECTs to flourish. However, inconsistent scoring between individuals and their levels of external, structural and internal well-being suggest that more research on the connection between mentoring and well-being of the ECTs. Social implications Work-life imbalance seems to be more challenging for ECTs than policymakers who provide these expectations are aware. Therefore, excessive work demands and intensive workloads need to be given proper attention for their potential negative effects (such as stress, burnout and absence) on the beginning teachers’ health and well-being. Likewise, purposeful strength-based approaches should be undertaken to establish generative and pro-social efforts to enhance the connectedness, collaboration, collegiality and resilience-building opportunities for novice professionals within flourishing learning communities. Originality/value In this paper, the authors have undertaken the first steps in exploring the impact that mentoring has on Canadian ECTs’ well-being. The study increases the understanding of how mentoring can be used as a purposeful strategy to support the well-being of ECTs and retain them in the teaching profession in Canada and potentially in different international contexts.